The development of an oral Newcastle disease vaccine - Ibrahim, A. Latif; Ideris, Aini; Spradbrow, Peter Bryan (1986)
An effective and simple method of vaccinating the free range village chickens against Newcastle disease was investigated. A heat resistant variants of the Australian V4 disease virus designated V4-UPM has been selected for use as an oral vaccine. The oral vaccine was prepared by spraying the heat resistant V4-UPM onto feed pellets. The potency of the vaccine is not affected when added to the pelleted feed. Chickens given the feed pellets vaccine at 3 and 6 weeks of age developed hemagglutination inhibition antibodies and were protected against challenge with the virulent Newcastle disease virus.